1994
DOI: 10.1029/94jd00573
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte effects on aqueous atmospheric oxidation of sulphur dioxide by ozone

Abstract: The kinetics of sulphur(IV) oxidation by ozone in an aqueous solution were studied in various supporting electrolytes (NaClO4, NaCl, NH4ClO4, Na2SO4), using the stopped flow method. The rate data in perchlorate medium (chosen as reference electrolyte) are empirically correlated by the following expression: r = −d[O3]/dt = k [O3] [S(IV)] [H+]−1/2. For each supporting electrolyte studied, the rate constant varies linearly with the ionic strength. The value of the rate constant is extrapolated to zero ionic stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Meanwhile, sulfate formation is a major source of acidity in aerosols, fog droplets, and cloud droplets (Calvert et al, 1985). In the absence of buffering, S(IV)→S(VI) oxidation pathways which are more effective at higher pH, such as oxidation of SO 2− 3 by O 3 (Maahs, 1983;Lagrange et al, 1994) or NO 2 (Lee and Schwartz, 1983;Clifton et al, 1988), will become quenched with increasing sulfate production ( Fig. 9, Supplement Sect.…”
Section: Interactions Of Aerosol and Cloud Chemistry With Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, sulfate formation is a major source of acidity in aerosols, fog droplets, and cloud droplets (Calvert et al, 1985). In the absence of buffering, S(IV)→S(VI) oxidation pathways which are more effective at higher pH, such as oxidation of SO 2− 3 by O 3 (Maahs, 1983;Lagrange et al, 1994) or NO 2 (Lee and Schwartz, 1983;Clifton et al, 1988), will become quenched with increasing sulfate production ( Fig. 9, Supplement Sect.…”
Section: Interactions Of Aerosol and Cloud Chemistry With Aciditymentioning
confidence: 99%
“…Smaller particles, typically made up of sulfate, nitrate, ammonium, and organic species, tend to be more acidic . Given that the composition of the CCN varies with size, then the fog/cloud solute composition will vary with drop size as observed in a variety of clouds and fogs (Noone et al, 1988;Ogren et al, 1989;Munger, 1989;Bator and Collett Jr., 1997;Laj et al, 1998;van Pinxteren et al, 2016;Moore et al, 2004;Guo et al, 2012a;Herckes et al, 2013).…”
Section: Ph Variation Across Drops Within a Cloud/fogmentioning
confidence: 99%
“…Potentially important atmospheric aqueous phase oxidants include O 3 , H 2 O 2 , HO 2 , OH, SO 4 − , Cl, Cl 2 − and NO 3 . Studies have found that O 3 and H 2 O 2 are the oxidants that are primarily responsible for aqueous phase SO 2 oxidation [ Botha et al , 1994; Erickson et al , 1977; Hoffmann , 1986; Kreidenweis et al , 2003, and references therein; Lagrange et al , 1994; Nahir and Dawson , 1987]. Two studies of the O 3 + DMS reaction [ Gershenzon et al , 2001; Lee and Zhou , 1994] demonstrated that the simultaneous uptake of DMS and O 3 and the subsequent surface reaction might play an important role in DMS oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The rate expression is thus of the form rka, rko, and rkc refer to the fraction of S(IV) in the form SO2aq, HSO•-, and SO•-, respectively. The numerical values for the respective rate coefficients are shown inTable 2.On the other hand,Penkett et al [1979] andLagrange et al [1994], who conducted measurements in the pH range 1 to 5.5, found that the reaction rate depended on the inverse square root of the hydrogen ion concentration. Botha et al…”
mentioning
confidence: 99%